Hyaluronic Acid/Gelatin-Based Multifunctional Bioadhesive Hydrogel Loaded with a Broad-Spectrum Bacteriocin for Enhancing Diabetic Wound Healing - Yin, Qi; Luo, Xue-Yue; Ma, Ke; Liu, Zhen-Zhen; Gao, Yu; Zhang, Jia-Bao; Chen, Wei; Yang, Yong-Jun (ACS applied materials & interfaces, 2024)
The development of multifunctional wound adhesives is critical in clinical settings due to the scarcity of dressings with effective adhesive properties while protecting against infection by drug-resistant bacteria. Polysaccharide and gelatin-based hydrogels, known for their biocompatibility and bioactivity, assist in wound healing. This study introduces a multifunctional bioadhesive hydrogel developed through dynamic covalent bonding and light-triggered covalent bonding, comprising oxidized hyaluronic acid, methacrylated gelatin, and the bacteriocin recently discovered by our lab, named jileicin (JC). The adhesion strength of the hydrogel, measured at 180 kPa, was 4.35 times higher than that of the fibrin glue. Furthermore, the hydrogel demonstrated robust platelet adhesion, procoagulant activity, and outstanding hemostatic properties in a mouse liver injury model. Incorporating JC significantly enhanced the phagocytosis and bactericidal capabilities of the macrophages. This immunomodulatory function on host cells, coupled with its potent bacterial membrane-disrupting ability, makes JC an effective killer against methicillin-resistant Staphylococcus aureus. In wound repair experiments on diabetic mice with infected full-thickness skin defects, the hydrogel treatment group showed a notable reduction in bacterial load, accelerated M2-type macrophage polarization, diminished inflammation, and hastened wound healing. Owing to its outstanding biocompatibility, antibacterial activity, and controlled adhesion, this hydrogel presents a promising therapeutic option for treating infected skin wounds.